Confessions of an AI Brain - Fersman, Elena; Pettersson, Paul.; Karapantelakis, Athanasios (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book explains the principles and applications of artificial intelligence for a broad audience. Artificial intelligence, as part of computer science, is often inspired by human intelligence. At the same time, there is still reluctance in the applications and usability of artificial intelligence among citizens. Industries are deploying AI in their products and processes but the level of maturity is varying. This book aims at reaching decision-makers and executives in companies, as well as the citizens and the academic community to explain the inner-workings of AI technology putting it in a center and giving it a human touch. The book is written as a first person narrative, from an AI perspective, having the AI brain tell the story.
Prologue -- Chapter 1: Baby steps -- Chapter 2: Basic Needs of an AI Brain -- Chapter 3: My Role in Internet of Things -- Chapter 4: Managing Relathionships -- Chapter 5: Working with Humans -- Chapter 6: Avoiding the Criminal Path -- Chapter 7: My Role in Climate Change -- Chapter 8: My Role in Diversity -- Chapter 9: My Creative Side -- Chapter 10: Growing Older and Staying in Shape -- Epilogue.
Keywords: Artificial intelligence; Computers and civilization; Robotics; Technology -- Moral and ethical aspects; Control engineering; Automation; Artificial Intelligence; Computers and Society; Robotics; Ethics of Technology; Control, Robotics, Automation